Supercritical fluid rectification of lignin microwave-pyrolysis oil. Issue 1 (18th September 2014) - Mudraboyina, B. P.; Fu, D.; Jessop, P. G.
Abstract : Supercritical fluid rectification selectively extracts single ring phenols from lignin microwave-pyrolysis oil. Abstract : A supercritical fluid rectification method (SFR) is described for selective extraction of single ring phenolic components from lignin microwave-pyrolysis oil. Supercritical CO2 at 35 °C and 8 MPa was used to extract phenols from the oil, after which the CO2 solution was passed up a column with a temperature gradient of 55–95 °C. SFR yielded up to 73% single ring phenolic components.